Fe-doped biomass-derived activated carbons as sustainable electrode materials in supercapacitors using different electrolytes - Mamaní, Arminda Noemí (2024)
In the search of sustainable and low-cost materials, able to reinforce circular economy, different activated carbons were obtained from agroindustry wastes, by means of a chemical activation route, after the doping of their corresponding biochars with Fe-based species through an incipient wetness method. These activated carbons were assessed as active electrode materials in supercapacitors using various electrolytic media, including aqueous, organic and ionic liquid electrolytes. The electrochemical results obtained revealed an excellent performance for all porous materials and electrolytes under evaluation, reaching the highest specific capacitance of 334F/g at a current density of 0.02 A/g using an aqueous electrolyte. The highest specific capacitance using an organic electrolyte and an ionic liquid electrolyte were 214F/g and 166F/g, respectively. It was found that activated carbons with a relevant mesopores volume, and pore sizes around 1 nm, achieved a better specific capacitance when using aqueous and organic electrolytes. However, heteroatoms as oxygen and iron enhanced the electrochemical performance of the device using the ionic liquid as electrolyte, thus achieving the highest energy and power density values (up to 63 Wh/kg and 1606 W/kg, respectively) among the different systems evaluated.